(Des) conceptual meetings in research in the areas of Education and Science Education: a focus on the state of art (Research, Society and Development, 2020)
This research aims to present the results of the bibliographic survey of works focus on the state of the art, in the areas of Education and Education in Sciences, from 1994 to 2018. As a result of this survey, we discussed some concepts related to the state of the art present in these works. To do so, we adopted as assumptions of a qualitative nature, such as bibliographic research. From the data collection sources we identified 44 works (10 theses, 3 dissertations and 31 scientific articles), published from 1994 to 2018, present in four databases: 1) Google Academic; 2) CAPES Dissertations and Theses Database; 3) Brazilian Digital Library of Theses and Dissertations (BDTD); 4) Proceedings of the National Research Meeting in Science Education (ENPEC). The results indicate that both the works in the area of Education and Education in Sciences point out the importance of the use of state of the art methods, in what concerns the mapping and description of the evolution of a certain academic production about a specific theme, with the main purpose of diagnosing possible gaps and perspectives of the investigated context, so that it may be based on and assist in the delineation of future researches that use this method.